Study of Cross-layer Design of the Shortest Path Routing and the SDMA in Wide-area Directed MANET - Kai, Tao; Ruiya, He (Recent Advances in Electrical & Electronic Engineering, 2025)
BackgroundTo satisfy the battle need, the information transmission delay of Mobile Ad Hoc Networks (MANETs) which are the neural network and information transmission channel for the modern battlefield must be lower. Therefore, the design of low-delay routing algorithms is of great significance for improving the operational capabilities of wide-area directional MANETs. The traditional routing algorithm design is mostly based on OSI/RM model, not on the global optimization, resulting in the algorithm not having adaptability and performance being far from optimal.ObjectiveAn algorithm named MNCR (MAC and Network Cross-layer Routing) based on cross-layer optimizing was proposed, which can finish the end-to-end data transmission with lower delay for some particular application like wide-area directed mobile ad hoc network (MANET) for a cooperative strike.MethodsThe proposed MNCR algorithm selected the shortest routing path based on the SDMA (Space Division Multiple Access) timetable applied and informed by MAC. When a packet arrived, the node computed all the possible paths and the corresponding delay according to the SDMA timetable and then selected the path with the lowest delay, which ensured that the packets were transmitted to the destination.ResultsThe theoretical analysis shows that the MNCR algorithm is less expensive than the classical shortest path algorithm. The simulation results show that the MNCR routing algorithm can save the end-to-end delay and ensure the real-time transmission of information. At the same time, the algorithm effectively balances the load of network nodes and overcomes the problem that the shortest path algorithm is prone to the “bottleneck effect”, which can effectively improve the reliability of information transmission.ConclusionThe proposed MNCR algorithm can finish the end-to-end data transmission with lower delay. So it has certain particular applications in wide-area directed mobile ad hoc networks (MANET) for cooperative strikes.
Keywords: MNCR